Red wolves - Gregory, Josh (Nature's children (New York, N.Y.), 2014)
"Once driven to the brink of extinction, the red wolf is in the midst of an incredible comeback story. Readers will find out how this resilient species survives in the wild, hunts for prey, and avoids contact with its greatest enemy: humans. They will also learn about red wolves canine relatives and discover how wildlife experts are working to increase the species wild population."--